Pachuco An American-Spanish Argot and Its Social Functions in Tucson, Arizona - Barker, George Carpenter (University of Arizona Press, 1969)
George Carpenter Barker's first major research project was field work in Tucson, Arizona on the function of language in a situation of culture contact. The results of his doctoral dissertation, "Social Functions of Language in a Mexican-American Community." The data and conclusions presented in his dissertation showed his perceptiveness in cross-cultural situations. He conducted additional field work on the social functions of language in cross-cultural situations in Tucson in 1947-48. This work centered around interviews with Mexican-American youths. Barker's quiet friendliness and understanding won the confidence of boys who were operating at the fringes, and who were his informants for this Pachuco study.